Mudança dos aspectos clínicos, laboratoriais e terapêuticos ao longo de 30 anos na leptospirose grave - Galdino, Gabriela Studart (2017)
Leptospirosis is a disease that has a huge variation of presenting symptoms. It may vary from a flu-like disease to critical presentation with life-threating complications, such as acute kidney injury (AKI). The aim of this study is to analize clinical, labolatorial data and outcomes in patients with leptospirosis in a 3 decade period and to enumerate the independent risk factor for death. Methods. A retrospective study was conducted including all patients with leptospirosis admitted to tertiary care hospitals in Fortaleza in the northeast of Brazil, between 1985 and 2015. Patients were divided into three groups according to the year of hospital admission: group I for the years 1985–1995, group II for 1996– 2005, and group III for 2006–2015. Demographic, clinical, and laboratory data were compared between the groups. The clinical manifestations, laboratory tests at admission and during hospital stay, as well as treatment, were evaluated. AKI was defined according to the KDIGO classification, and the patients in each category were compared. Statistical analysis was done with SPSS program version 23.0. Results. A total of 526 patients were included. Their mean age was 37.3 ± 15.9 years and 82.4% were male. The mean time between symptom onset and admission was 7 ± 4 days. There was a linear decrease in the levels of serum urea (190.1 ± 92.7, 135 ± 79.5, and 95.6 ± 73.3 mg/dl, respectively, p < 0.0001) and creatinine (5.8 ± 2.9, 3.8 ± 2.6, and 3.0 ± 2.5 mg/dl, respectively, p < 0.0001) in each decade, while levels of hemoglobin (10.3 ± 1.9, 10.8 ± 2.0, and 11.5± 2.1 g/dl, respectively, p < 0.0001) and platelets (57.900 ± 52.650, 80.130 ± 68.836, and 107.101 ± 99.699x109/L, respectively, p < 0.0001) increased. The use of antibiotics increased progressively (43,8%, 80,8% e 94,5%, p < 0,0001).There is a tendency towards a linear decrease in mortality (22%, 14%, and 11.6%, respectively, p = 0.060). Age, diastolic blood pressure and direct billirrubin were independent risk factors for death. Conclusions. Leptospirosis showed significant changes over time in this region. The main changes point to a decrease in disease severity and complications, such as acute kidney injury. Mortality has decreased progressively.